A process for error correction for strength and conditioning coaches - Cushion, E.; Howe, L.; Read, P.; Spence, A. (Strength and Conditioning Journal, 2017)
There are several skill acquisition strategies available to coaches when correcting a movement error. However, it is not always clear which strategies should be used for a situation and in what order. This article aims to provide coaches with a logical evidence-based process to assist their coaching practice. In addition to a proposed model of error correction, examples are provided for several commonly occurring situations in strength and conditioning practice.